ANALYSIS OF SIGNAGE AVAILABILITY AND ITS OPTIMIZATION IN THE DEPARTURE AREA OF SAMS SEPINGGAN INTERNATIONAL AIRPORT - Gallis Nawang Ginusti; Sintya Ika Windiyani (Sekolah Tinggi Teknologi Kedirgantaraan, 2023)
The operational efficiency of an airport is supported by facilities, one of which is information service facilities in the form of signage for the convenience and ease of airport service users. This study aims to investigate the availability of signage, the supervision and handling processes of TSO personnel as the ones who are responsible for the availability and readiness of facilities in the airport terminal, and how TSO personnel follow up on signage optimization. This was descriptive qualitative research approach with both primary and secondary data sources. Data collection techniques include interviews, observations, and document analysis, while data analysis techniques involve data reduction, data display, drawing conclusions, and verification. Data validity and reliability were ensured through source triangulation and technique triangulation. The research findings revealed that the departure area of SAMS Sepinggan Airport has Operational, Public Facilities, Warning, and Prohibition, however Office signage is noticeably absent. Several signage elements do not perform their intended functions optimally due to their poor positioning or layout and fading information. TSO personnel have appropriately followed the prevailing quality procedures for supervision and management by initiating the submission of reports, which, if approved, leads to the renewal of signage in accordance with the applicable regulations and if not, TSO personnel will implement mitigation measures by installing standing signs and requesting assistance from the Customer Service Unit to guide service users in locating positions and areas in the departure area.